TREN DAN STRATEGI MARKETING POLITIK DALAM ERA DIGITAL: SEBUAH STUDI LITERATUR DENGAN FOKUS PENDIDIKAN DI SEKOLAH - Lestari, Anggre Fani; Asrinaldi, Asrinaldi; Putri, Indah Adi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research on "Political Marketing Trends and Strategies in the Digital Era: A Literature Study" includes several important aspects aimed at understanding and analyzing political marketing practices in the context of digital technology. This type of research is a literature study which involves searching and analyzing relevant theoretical references from various sources such as books, scientific articles, research reports, journals and previous studies. The study results show that in the current digital era, political marketing strategies have evolved to become more complex and innovative by utilizing social media such as Facebook, Twitter, Instagram and YouTube to not only spread campaign messages widely, but also to interact directly with voters, getting direct feedback, and build a more personal relationship. Analytics and big data technology also play a key role in identifying potential voter segments and tailoring campaign messages according to their preferences and behavior. However, challenges such as the spread of fake news and disinformation highlight the need for an honest approach, integrity and transparency in political practice. Overall, the digital era brings great potential for innovation in political marketing by creating a more engaged and relevant experience for voters, while addressing challenges such as the use of algorithms and big data technology. Literature studies on political marketing trends and strategies in the digital era, especially in the context of school education, emphasize the importance of preparing the younger generation with the necessary technological skills and developing critical political awareness. This kind of education is key to increasing participation in a democratic process that is increasingly digitally connected and facing new dynamics in political marketing strategies.